Untapped bacterial diversity and metabolic potential within Unkeshwar hot springs, India - Mehetre, Gajanan T. (Archives of Microbiology, 2018)
Hot springs support diverse and interesting groups of microorganisms adapted to extreme conditions and gaining attention in biotechnological applications. However, due to limitations of cultivation methods, a majority of such extremophiles remain uncultivated and unexplored. The advent of multiple cultivation conditions and specialized culture media could possibly aid to access the unexplored microbial portion of hot springs. In the present study, different media and isolation strategies were applied to isolate hitherto unexplored bacterial taxa in the water samples collected from Unkeshwar hot springs, India. Molecular, phylogenetic and predictive functional characterization of the isolated bacterial population was done using 16S rRNA sequencing coupled with Tax4Fun tools. Furthermore, representative isolates were screened for important enzymes (cellulase, xylanase, amylase, and protease) and heavy metal tolerance (chromium, arsenic) properties. A total of 454 bacterial isolates obtained were mapped into 57 unique bacterial genera and 4 different bacterial phyla. Interestingly, 37 genera not previously isolated from Indian hot springs, were isolated for the first time in the present study. However, most of these genera (23 out of 37) were reported only in metagenomics studies from Indian and global hot springs. Furthermore, around 14 genera not previously cultivated and not detected in metagenomics studies of hot springs are documented here. The metabolic potential was ascertained by determining the abundance of specific genes using in silico based Tax4Fun tool, which identified around 315 metabolic pathways for metabolism of carbohydrates, synthesis of secondary metabolites and degradation of xenobiotic compounds. Bioprospection study revealed that 33 and 25 bacterial genera were positive for enzyme production and resistance to the heavy metals, respectively. The present study revealed the advantages of cultivation methods using a comprehensive multiple isolation approach for exploring untapped and unique bacterial diversity, and also utilities for various biotechnological and environmental applications.
Keywords: Bacterial diversity; Bioprospecting; Cultivation; Heavy metals; Untapped

Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Spatio-temporal variation of the microbiome and resistome repertoire along an anthropogenically dynamic segment of the Ganges River, India - Samson, Rachel; Rajput, Vinay; Yadav, Rakeshkumar; Shah, Manan; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Science of the Total Environment, 2023)
Aquatic ecosystems are regarded as a hub of antibiotic and metal resistance genes. River Ganges is a unique riverine system in India with socio-cultural and economic significance. However, it remains underexplored for its microbiome and associated resistomes along its anthropogenically impacted course. The present study utilized a nanopore sequenc-ing approach to depict the microbial community structure in the sediments of the river Ganges harboring antibiotic and metal resistance genes (A/MRGs) in lower stretches known for anthropogenic impact. Comprehensive microbiome analyses revealed resistance genes against 23 different types of metals and 28 classes of antibiotics. The most dominant ARG category was multidrug resistance, while the most prevalent MRGs conferred resistance against copper and zinc. Seasonal differences dismally affected the microbiota of the Ganges. However, resistance genes for fosmidomycin and tetracycline varied with season ANOVA, p < 0.05. Interestingly, 333 and 334 ARG subtypes were observed at all the locations in pre-monsoon and post-monsoon, respectively. The taxa associated with the dominant ARGs and MRGs were Pseudomonas and Burkholderia, which are important nosocomial pathogens. A substantial phage diversity for pathogenic and putrefying bacteria at all locations attracts attention for its use to tackle the dissemination of antibiotic and metal-resistant bacteria. This study suggests the accumulation of antibiotics and metals as the driving force for the emergence of resistance genes and the affiliated bacteria trafficking them. The present metagenomic as-sessment highlights the need for comprehensive, long-term biological and physicochemical monitoring and mitigation strategies toward the contaminants associated with ARGs and MRGs in this nationally important river.
Keywords: Antibiotics (ARGs); Bacteriophages; Heavy metals (MRGs); Metagenomics; Microbiome; River Ganges